Tourism National Program in Conflict Countries: Cases of Western Balkans - Karima, Shofi; Tairas, David Ronald (Global Writing Academica Researching & Publishing, 2024)
Cultural differences, economic and social development, and demographic trends among the countries of the Western Balkans are the causes of the conflict. This research focuses on tourism development strategies in conflict countries in the Western Balkans. This study raises the question of how conflict states develop long-term strategies for sustainable tourism. The method used is exploratory (qualitative) which produces a tourism development strategy. The theory used is sustainable tourism by Ramon Adillon using seven elements for sustainable tourism development. The result shows there is a correlation and mutual support between each of the main components of the ‘Diamond Sustainable’ as well as the main components and supporting factors. This research shows that they have strengths and opportunities that can be optimized as a strategy to maintain tourism, on the other hand, the existence of weaknesses and threats can hinder the sustainability of tourism in the Western Balkan.